Effects of acupuncture on the pregnancy outcomes of frozen-thawed embryo transfer: A systematic review and meta-analysis - Zhu, Can; Xia, Wanting; Huang, Jinzhu; Zhang, Xuan; Li, Fangyuan; Yu, Xiaorun; Ma, Jiamin; Zeng, Qian (Frontiers in Public Health, 2022)
Background Acupuncture is increasingly used as adjuvant therapy for infertile women undergoing frozen-thawed embryo transfer (FET); however, its effects and safety are highly controversial. This study aimed to evaluate the pooled effects of adjuvant acupuncture on FET pregnancy outcomes. Methods We considered only randomized controlled trials (RCTs) that compared acupuncture with sham acupuncture or no adjuvant treatment during FET and the primary outcome was clinical pregnancy rate. Two authors separately selected studies, extracted data, and performed a risk of bias assessment. Pooled data were expressed as risk ratio (RR) or mean difference (MD), with a 95% confidence interval (CI). In addition, we conducted subgroup and sensitivity analyses to investigate the sources of heterogeneity, and we also constructed funnel plots to assess the likelihood of publication bias. Finally, Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) was applied to evaluate the quality of evidence. Results A total of 14 RCTs with a total of 1,130 participants were included in the study. We found significant effects of acupuncture adjuvant to FET on the outcomes of clinical pregnancy rate (RR = 1.54, 95% CI [1.28, 1.85], I2 = 34%; 14 trials), biochemical pregnancy rate (RR = 1.51, 95% CI [1.21, 1.89]; 5 trials), endometrial thickness (MD = 0.97, 95% CI [0.43, 1.51]; 12 trials), and endometrial pattern (RR = 1.41, 95% CI [1.13, 1.75]; 7 trials). For live birth rate (RR = 1.48, 95% CI [0.90, 2.43], 4 trials), there were no statistical effectiveness. For subgroup analyses, most variables had tolerable heterogeneity (I2 = 0%) except for trials that were sham-controlled, performed acupuncture only after FET, or <5 times, which appeared to interpret most of the heterogeneity. Additionally, the quality of evidence of all outcomes in this review ranged from low to moderate. Conclusion Acupuncture could be instrumental in the pregnancy outcomes of FET, and has very few risks of severe adverse events; however, the quality of evidence is unsatisfactory. Further research with rigorous methodological quality should be considered, and the protocols of acupuncture also need more investigations (e.g., appropriate control groups, sessions, and times).